Peningkatan Kemampuan Penggunaan Jeda dalam Membaca Lancar Menggunakan Model Oral Reading Fluency di Kelas II Sekolah Dasar - Aprilia, Tri Windi; Chandra, Chandra (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2024)
This research was motivated by the problem of reading fluently by students who were still unable to use pauses in class II of elementary school. In fact, some students still cannot read. This research aims to describe improving the ability to read fluently using pauses using the Oral Reading Fluency (ORF) model for class II students at SDN 20 Indarung, Padang City. This type of research is classroom action research, using qualitative and quantitative approaches. Research procedures consist of planning, implementation, observation and reflection. The subjects of this research were class II students at SDN 20 Indarung, Padang City. The data sources for this research are the learning process (observation of activities or behaviour of teachers and students) and fluent reading ability using the Oral Reading Fluency (ORF) model. The results of the study showed an increase in the ability to read fluently at of class II students. Previously, students had not been able to use pauses in reading. After implementing the Oral Reading Fluency model, students' ability to read fluently has increased. More than half of the students can make pauses between phrases, pauses between clauses, pauses between utterances, pauses between sentences, and pauses without punctuation.